Combined raw cornstarch and nifedipine as an additional treatment in persistent hyperinsulinemic hypoglycemia of infancy - Chittiwat Suprasongsin (2018)
This study reports the result of treatment with the combination of raw cornstarch and nifedipine in two infants affected with hyperinsulinemic hypoglycemia of variable severity. The first infant developed hypoglycemia during early neonatal period and required subtotal pancreatectomy. She still developed hypoglycemia after her second operation. The second infant developed hypoglycemia at the age of 7 months. Raw cornstarch and nifedipine efficiently normalized both infants' blood glucose levels. Although they still need frequent feedings, no hypoglycemic episode was reported except when they were sick. Their growth and development were markedly improved after initiation of treatment.